An overview of cephalosporin antibiotics as emerging contaminants: a serious environmental concern - Das, Nilanjana (3 Biotech, 2019)
Antibiotics have been categorized as emerging pollutants due to their indiscriminate usage, continuous input and persistence in various environmental matrices even at lower concentrations. Cephalosporins are the broad-spectrum antibiotics of β-lactam family. Owing to its enormous production and consumption, it is reported as the second most prescribed antibiotic classes in Europe. The cephalosporin wastewater contains toxic organic compounds, inorganic salts, and active pharmaceutical ingredients (API) which pose a potential threat to the organisms in the environment. Therefore, removal of cephalosporin antibiotics from the environment has become mandatory as it contributes to increase in the level of chemical oxygen demand (COD), causing toxicity of the effluent and production of cephalosporin-resistant microbes. So far, several processes have been reported for degradation/removal of cephalosporins from the environment. A number of individual studies have been published within the last decade covering the various aspects of antibiotics. However, a detailed compilation on cephalosporin antibiotics as an emerging environmental contaminant is still lacking. Hence, the present review intends to highlight the current ecological scenario with respect to distribution, toxicity, degradation, various remediation technologies, and the regulatory aspects concerning cephalosporins. The latest successful technologies for cephalosporin degradation/removal discussed in this review will help researchers for a better understanding of the nature and persistence of cephalosporins in the environment along with the risks associated with their existence. The research thrust discussed in this review will also evoke new technologies to be attempted by the future researchers to develop sustainable options to remediate cephalosporin-contaminated environments.